Ophthalmic artery originating from contralateral internal carotid artery associated with ipsilateral agenesis of internal carotid artery - Takaki Hamada; Daisuke Itoh; Wataro Tsuruta; Satoshi Nakamura; Tomohiko Masumoto (Radiology Case Reports, 2024)
Congenital absence of the internal carotid artery is a rare anatomical variant. The primarily reported origins of the ophthalmic artery associated with this variant are the posterior communicating, middle cerebral, and external carotid arteries. We report the case of a patient without an internal carotid artery whose ophthalmic artery originated from the contralateral internal carotid artery. The superior hypophyseal and prechiasmal arteries may contribute to collateral flow to the orbit from the contralateral internal carotid artery.